Three tales of yore - Wurfel, Marlene (My University, 2020)
Three of Aesop's fables re-told and re-arranged by Marlene Wurfel for kids: The Donkey in the Lion's Skin, The Crow and the Pitcher, and The Milkmaid and the Pail. Aesop was one of the sages of Ancient Greece, like Socrates. The stories ascribed to him are thousands of years old (all dating to at least 600 b.c.) and are called fables because they always include a moral lesson. Storytellers are always philosophers at heart, and so are kids.
Keywords: storytelling; children's stories; fables